Principles of Decoration in the Roman World - Haug, Annette; Taylor Lauritsen, M. (Decorative Principles in Late Republican and Early Imperial Italy (Decor), 2021)
Principles of Decoration in the Roman World explores the manner in which architectural settings and action contexts influenced the perception of decorative elements in Roman culture. By examining the relationship between viewer, setting and medium through the lens of decor, the Roman concept of appropriateness, the papers in this volume shed new light on the decorative principles employed across Roman Italy and beyond.